The James Hutton Institute Launches New 'IPM@Hutton' Research Centre and Website. (1st December 2017) - Birch, Nick
The James Hutton Institute (JHI), formed by merger of 2 institutes in 2011 (Scottish Crops Research Institute (SCRI) and Macaulay Institute), has actively researched many different areas and aspects of crop protection since the founding of one of the forerunner institutes, the Scottish Crop Research Institute, Dundee. Research covers IPM disciplines included plant breeding, crop genetics, entomology, pathology, ecology and chemistry. Over the intervening period since the formation of Scotland's largest research institute, employing more than 500 scientists and support staff, it has been in large EU projects including PURE, ENDURE and AMIGA, pulling together its joint expertise and experience. The aim is to reduce farmers' reliance on pesticides with other options from an 'IPM toolbox' which is flexible and fine-tuned for each cropping system and region. For Scotland, this means a JHI research focus on IPM strategies for soft fruit, cereals and potato. At The James Hutton Institute's IPM Centre (IPM@Hutton), the vision is to be at the forefront of innovative and transformative science for sustainable management of land, crop and natural resources that supports thriving communities. IPM is an essential component of this vision. JHI carries out its crop protection research in multiple areas both to generate and improve specific IPM tools, and to combine together components of sustainable integrated pest management to create toolboxes of flexible solutions, that when deployed together, are more effective. It works closely with farmers, crop advisors, the crop protection industry and consumer groups to ensure that our future IPM tools and toolboxes are safe, effective, adaptable and practical.